Antihyperglycemic and Antilipidemic Effects of the Ethanol Extract Mixture of Ligularia fischeri and Momordica charantia in Type II Diabetes-Mimicking Mice. (2nd October 2018) - Baek, Hyun Jin; Jeong, Yong Joon; Kwon, Jeong Eun; Ra, Jong Sung; Lee, Sung Ryul; Kang, Se Chan
Abstract : The extract of the Momordica charantia fruit (MCE) is recognized as an alternative treatment for diabetes. The extract of Ligularia fischeri leaves (LFE) is traditionally used as a folk medicine for treating inflammatory diseases in Korea as well. In this study, we investigated the synergistic effect of MCE combined with LFE on antihyperglycemic and antihyperlipidemic potentials. Based on the α -glucosidase inhibitory effect and promotion of adipocyte differentiation in the 3T3-L1 cell line, the MLM was prepared with MCE:LFE (8:2 weight:weight). MLM showed the synergistic effects in the promotion of the glucose uptake rate, suppression of dipeptidyl peptidase-4 (DPP-4) mRNA expression, upregulation of an insulin receptor substrate and glucose transporter type-4 expression, and an increase in insulin-associated signaling in C2C12 cells. In addition, the efficacy of peroxisome proliferator-activated receptor- γ agonism and glucose uptake rate by MLM supplementation was significantly enhanced in vitro . Then, the antihyperglycemic and antihyperlipidemic effects of MCE, LFE, and MLM at the dose of 50, 100, and 200 mg/kg/day (n = 6 per each group) were determined in streptozotocin (STZ)-insulted mice fed an atherogenic diet (ATH) for 4 weeks. In addition, MLM (50, 100, and 200 mg/kg/day, n = 5 per each group) was supplemented in ATH-fed db/db mice for 10 weeks. Compared with MCE or LFE alone, MLM supplementation led to a more significant reduction of glucose levels in both STZ/ATH and db/db /ATH mice as well as lowered lipid profiles in STZ/ATH mice. In addition, the stimulation of islet of Langerhans regeneration was more pronounced by MLM supplementation in both mice models. In conclusion, antihyperglycemic and antihyperlipidemic effects were strengthened by the combined extracts of L. fischeri and M. charantia (MLM) in diabetes-mimicking mice.